ANALISIS MARKETING PADA PEMBIAYAAN MURABAHAH DI BMT AGAM MADANI NAGARI KAPAU - Siti Aisyah; Sofia Ridha (Adisam Publisher, 2024)
This research is motivated by the indication of the lack of public understanding of Murabahah financing at BMT Agam Madani Nagari Kapau and the ineffectiveness of marketing activities carried out by BMT Agam Madani Nagari Kapau to the community. The purpose of this study is to determine the marketing steps for Murabahah financing products at BMT Agam Madani Nagari Kapau and to determine whether the implementation of Murabahah financing has been effective and in accordance with existing theories. The type of research used in this study is field research with a descriptive qualitative approach. This study uses primary and secondary data sources, with data collection techniques of interviews, observation and documentation. The informants in this study were Mr. Mustir, A.Md as the head of BMT Agam Madani Nagari Kapau, Mrs. Fetri Dewi S.E. as the Head of Marketing, and customers of BMT Agam Madani Nagari Kapau Murabahah financing products. This study uses data analysis techniques such as data reduction, data presentation, and drawing conclusions to support the popularity of Murabahah financing in Kapau City and its surroundings. BMT Agam Madani Kapau implements a marketing strategy that includes SWOT analysis and marketing mix to promote Sharia-compliant Murabahah financing products. Its marketing strategies include flexible pricing, location strategies, promotional efforts, employee training, and an easy and fast financing application process to attract customers effectively and efficiently.